Strategi Guru Bahasa Indonesia pada pembelajaran berbasis teks sebagai pengembangan kemampuan berpikir Siswa SMA Negeri Di Kota Pontianak - Syam, Christanto; Olendo, Yudhistira Oscar; Putra, Zakarias Aria Widyatama (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Text as a means of learning Indonesian may be developed and conditioned in such a manner that it can be a successful technique for Indonesian language teachers. Understanding text-based Indonesian learning materials takes extensive preparation and conditioning on the part of students. Purpose of this study is to analyse, comprehend, and characterise the process of text-based Indonesian language acquisition as it is implemented by instructors at public high schools in Pontianak City. This study, which used a descriptive approach with a qualitative form, also targeted Indonesian language instructors by selecting five public high schools in Pontianak as a representative sample. Direct observation and interview approaches were utilised to collect data, with data collecting devices in the form of observation sheets and interview lists. Furthermore, triangulation techniques were used in the last step of the data analysis process to test the validity of new data utilising data collecting, data condensation, data presentation, and conclusion drawing. Based on the findings of observations and interviews, it was discovered that Indonesian instructors' text-based learning methodologies may more effectively and efficiently establish an environment conducive to Indonesian language acquisition. Because students may undertake a detailed examination and analysis of a text, their comprehension of its structure and linguistic qualities is more in-depth and thorough. This research can also provide studies and has for the Merdeka Belajar curriculum to continue to provide recommendations for text-based Indonesian language learning strategies so that learning indicators and objectives can be achieved.